A randomized controlled clinical trial of prazosin for alcohol use disorder in active duty soldiers: Predictive effects of elevated cardiovascular parameters. (21st February 2023) - Raskind, Murray A.; Williams, Tammy; Holmes, Hollie; Hart, Kim; Crews, Laura; Poupore, Eileen L.; Thomas, Ronald G.; Darnell, Jolee; Daniels, Colin; Goke, Kevin; Hendrickson, Rebecca; Terry, Garth; et al.
Abstract: Background: Excessive noradrenergic signaling contributes to aversive symptoms of alcohol withdrawal that interfere with abstinence or reductions in harmful use. Methods: To address this aspect of alcohol use disorder, 102 active‐duty soldiers participating in command‐mandated Army outpatient alcohol treatment were randomized to also receive the brain‐penetrant alpha‐1 adrenergic receptor antagonist prazosin or placebo for 13 weeks. Primary outcomes were scores on the Penn Alcohol Craving Scale (PACS), standard drink units (SDUs) per day averaged over each week, % days of any drinking per week, and % days of heavy drinking per week. Results: PACS declines did not differ significantly between the prazosin and placebo groups in the overall sample. In the subgroup with comorbid PTSD ( n  = 48), PACS declines were significantly greater in the prazosin than in the placebo condition ( p  < 0.05) . Baseline alcohol consumption was markedly reduced by the pre‐randomization outpatient alcohol treatment program, but the addition of prazosin treatment produced a greater slope of decline in SDUs per day compared to placebo ( p  = 0.01). Preplanned subgroup analyses were performed in soldiers with elevated baseline cardiovascular measures consistent with increased noradrenergic signaling. In soldiers with elevated standing heart rate ( n  = 15), prazosin reduced SDUs per day ( p  = 0.01), % days drinking ( p  = 0.03), and % days heavy drinking ( p  = 0.001) relative to placebo. In soldiers with elevated standing systolic blood pressure ( n  = 27), prazosin reduced SDUs per day ( p  = 0.04) and tended to reduce % days drinking ( p  = 0.056). Prazosin also reduced depressive symptoms and the incidence of emergent depressed mood more than placebo ( p  = 0.05 and p  = 0.01, respectively). During the final 4 weeks of prazosin vs. placebo treatment that followed completion of Army outpatient AUD treatment, alcohol consumption in soldiers with elevated baseline cardiovascular measures increased in those receiving placebo but remained suppressed in those receiving prazosin. Conclusions: These results extend reports that higher pretreatment cardiovascular measures predict beneficial effects of prazosin, which may be useful for relapse prevention in patients with AUD. Abstract : 102 soldiers with Alcohol Use Disorder already in outpatient treatment were randomized to the alpha‐1 adrenoreceptor antagonist prazosin or placebo for 13 weeks. In soldiers with elevated baseline heart rate or blood pressure suggestive of alcohol withdrawal, prazosin reduced alcohol consumption significantly more than did placebo. During the final 4 weeks that followed completion of outpatient treatment, soldiers with elevated baseline heart rate randomized to placebo increased alcohol consumption but those randomized to prazosin remained abstinent, consistent with relapse prevention.